Environmental risk factors of Wilms tumour: A systematic review and meta-analysis - Felix M. Onyije; Roya Dolatkhah; Ann Olsson; Liacine Bouaoun; Joachim Schüz (EJC Paediatric Oncology)
Wilms tumour (WT) is the fourth leading cause of cancer death in children. Elucidating modifiable risk factors is crucial in identifying venues for primary prevention of the disease. This study aimed to review literature and synthesize environmental risk factors for WT. We conducted a systematic review and meta-analysis of epidemiological studies using PubMed, Web of Science, and Embase databases. Studies were included if they were case-control or cohort studies of children under the age of 20 years at diagnosis and reported Relative Risks (RRs) with 95 % confidence intervals (CIs). Pooled effect sizes (ES) and 95 % CIs for risk factors associated with WT were estimated using random-effects models. We included 58 eligible studies from Asia, Europe, Latin and North America, and Oceania totalling approximately10000 cases of WT diagnosed between 1953 and 2019. We confirmed an association between high birthweight ((>4000 g) ES 1.54, CI 1.20–1.97) and WT. Similarly, consistent associations were suggested for Caesarean section (ES 1.23, CI 1.07–1.42), gestational age <37 weeks (ES 1.45, CI 1.21–1.74), and large-for-gestational age (ES 1.52, CI 1.09–2.12). Parental occupational exposure to pesticides during preconception / pregnancy also showed increased risks of WT (maternal ES 1.28, CI 1.02–1.60, paternal ES 1.48, CI 0.98–2.24). There were inverse associations for breastfeeding (ever breastfed = ES 0.71, CI 0.56–0.89; < 6 months ES 0.67, CI 0.49–0.91; and ≥6 months ES 0.75, CI 0.59–0.97), and maternal intake of vitamins (unspecified) and folic acid during pregnancy (ES 0.78, CI 0.69–0.89). Among factors showing no associations were low birthweight (<2500 g), small-for-gestational age, assisted reproductive technology, parental age, and smoking or alcohol consumption during preconception / pregnancy, paternal occupational extremely low frequency magnetic fields (ELF-MF) exposures, and maternal X-ray exposure during pregnancy. Our findings suggest that modifiable risk factors of WT are parental occupational exposure to pesticides, breastfeeding (beneficial), and intake of folic acid during preconception / pregnancy (beneficial), but all associations were rather modest in strength.